Identifying seepage pathways through an embankment dam using electrical and electromagnetic geophysical methods - Warden, Camilla, author; Sanford, William E., advisor; McGrath, Daniel, committee member; Bailey, Ryan T., committee member (Colorado State University. Libraries, 2024)
In the 1950's, increased water supply demands resulted in a construction project at the earth and rockfill embankment Little Wood River Dam to increase the reservoir water capacity. After the enlargement of the structure from 1958 to 1960, seepage was observed in the auxiliary spillway channel, vicinity of the downstream toe, and downstream on river left. In earth and rockfill embankment dams, seepage can manifest as internal erosion, or "piping", which may compromise the structural integrity of the embankment over time. Though no symptoms of internal erosion were observed, seepage monitoring weirs reported a significant increase in seepage flow rate when the reservoir surpasses a particular "critical" elevation or was at high pool conditions. As a result, the United States Bureau of Reclamation, the operator of the dam, opted to do a comprehensive site review to identify potential seepage pathways and determine if remediation were necessary. This geophysical study was designed to compare survey results to see if there was a change in subsurface saturation from low to high pool, that may indicate the presence of a seepage pathway originating at the reservoir. Additionally, this investigation also explored the groundwater conditions at the study area to determine if regional groundwater flow was contributing to observed seepage. Electrical and electromagnetic near-surface geophysical surveys were conducted in September 2021 (low pool) and June 2023 (high pool) and compared as timelapse to show any changes in subsurface bulk electrical resistivity distribution that could be attributed to change in moisture content or a seepage pathway that becomes active due to the increased hydraulic gradient from high pool reservoir conditions. Repeated Electrical Resistivity Tomography and Frequency Domain Electromagnetic surveys were conducted during low and high pool, and a Streaming Potential survey and Saltwater Injection Tracer Test were conducted during high pool only. Findings revealed that seepage originating at the reservoir travels through the left abutment and main embankment through a discontinuity between the dam enlargement material and underlying unit. Seepage from the reservoir contributes to the seepage seen in the auxiliary spillway channel and in the vicinity of the downstream toe. Regional groundwater flow from outside the reservoir footprint also contributes to observed seepage in the auxiliary spillway channel, vicinity of the downstream toe, and downstream on river left. Results of this geophysical study allowed for the delineation of seepage pathways through the left abutment and main embankment, providing a valuable contribution to the larger comprehensive review that will determine if future work to the structure is necessary. Regional groundwater was found to be a contributor to all observed seepage which may result in the extension or installation of concrete cutoff walls designed to prevent flow. Locations of observed seepage pathways can be individually targeted for remediation such as trenching and backfilling with impervious materials, and other observed seepage zones can be strategically monitored and maintained. Increasing the timelapse survey coverage to include average water level conditions could further improve the results and delineate if seepage observed below the critical elevation were being contributed to solely by groundwater flow. This timelapse technique paired with multiple electrical and electromagnetic geophysical methods provided extensive data coverage and excellent data quality that could be utilized for similar seepage studies.